EMA Review of Acalabrutinib for the Treatment of Adult Patients with Chronic Lymphocytic Leukemia. (10th February 2021) - Delgado, Julio; Josephson, Filip; Camarero, Jorge; Garcia‐Ochoa, Blanca; Lopez‐Anglada, Lucia; Prieto‐Fernandez, Carolina; Hennik, Paula B. van; Papadouli, Irene; Gisselbrecht, Christian; Enzmann, Harald; Pignatti, Francesco
Abstract: : On November 5, 2020, a marketing authorization valid through the European Union (EU) was issued for acalabrutinib monotherapy or acalabrutinib in combination with obinutuzumab (AcalaObi) in adult patients with treatment‐naïve (TN) chronic lymphocytic leukemia (CLL) and also for acalabrutinib monotherapy in adult patients with relapsed or refractory (RR) CLL. Acalabrutinib inhibits the Bruton tyrosine kinase, which plays a significant role in the proliferation and survival of the disease. Acalabrutinib was evaluated in two phase III multicenter randomized trials. The first trial (ACE‐CL‐007) randomly allocated acalabrutinib versus AcalaObi versus chlorambucil plus obinutuzumab (ChlObi) to elderly/unfit patients with TN CLL. The progression‐free survival (PFS), as assessed by an independent review committee, was superior for both the AcalaObi (hazard ratio [HR], 0.1; 95% confidence interval [CI], 0.06–0.17) and acalabrutinib (HR, 0.2; 95% CI, 0.13–0.3) arms compared with the ChlObi arm. The second trial (ACE‐CL‐309) randomly allocated acalabrutinib versus rituximab plus idelalisib or bendamustine to adult patients with RR CLL. Also in this trial, the PFS was significantly longer in the acalabrutinib arm (HR, 0.31; 95% CI, 0.20–0.49). Adverse events for patients receiving acalabrutinib varied across trials, but the most frequent were generally headache, diarrhea, neutropenia, nausea, and infections. The scientific review concluded that the benefit‐risk ratio of acalabrutinib was positive for both indications. This article summarizes the scientific review of the application leading to regulatory approval in the EU. Implications for Practice: Acalabrutinib was approved in the European Union for the treatment of adult patients with chronic lymphocytic leukemia who have not received treatment before and for those who have received therapy but whose disease did not respond or relapsed afterward. Acalabrutinib resulted in a clinically meaningful and significant lengthening of the time from treatment initiation to further disease relapse or patient's death compared with standard therapy. The overall safety profile was considered acceptable, and the benefit‐risk ratio was determined to be positive. Abstract : This article summarizes the EMA scientific review of the application leading to regulatory approval for acalabrutinib for treatment of leukemia.